2020
DOI: 10.1186/s13063-020-04599-2
|View full text |Cite
|
Sign up to set email alerts
|

Fire needle plus cupping for acute herpes zoster: study protocol for a randomized controlled trial

Abstract: Background: Acute herpes zoster (AHZ) is a common skin disease caused by invasion of the varicella zoster virus into the ganglia and skin, and the severe pain is the most complaint, which can seriously disturb the normal life of patients. Fire needle plus cupping is a special acupuncture treatment, which is widely used to treat AHZ for its better analgesic effect in China although it has not been fully verified by rigorous randomized controlled trial (RCT). Methods/design: To test the effect, a three-arm rando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The means and standard deviation of total score: 6 ± 2.3. Items are scored as present (1) or absent (0), and a total score is obtained by summation. For example, the item "dropout" is scored 1 if the dropout rate is <15%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The means and standard deviation of total score: 6 ± 2.3. Items are scored as present (1) or absent (0), and a total score is obtained by summation. For example, the item "dropout" is scored 1 if the dropout rate is <15%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 65 ] The effect of heavy metals, such as Cadmium, has been shown to damage kidneys and cause back pain. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the VAS score of acupuncture and moxibustion combined with cupping for PHN was significantly lower than that of conventional western medicine treatment. The mechanism of acupuncture and moxibustion combined with cupping in the treatment of PHN may be to regulate the function of local blood vessels and muscles by stimulating local nerves, reducing the symptoms of local smooth muscle spasm, and then exerting a good analgesic effect [41] . In the meta-analysis of Pei et al, [40] it has been found that acupuncture can significantly relieve PHN.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of acupuncture and moxibustion combined with cupping in the treatment of PHN may be to regulate the function of local blood vessels and muscles by stimulating local nerves, reducing the symptoms of local smooth muscle spasm, and then exerting a good analgesic effect. [41] In the meta-analysis of Pei et al, [40] it has been found that acupuncture can significantly relieve PHN. Our research further supports the application of Chinese medicine in the treatment of PHN.…”
Section: Discussionmentioning
confidence: 99%